PEMBUATAN SENYAWA AMINA SEKUNDER DENGAN PROSES HIDROGENASI SENYAWA NITRIL - Hilyati Hilyati; Siti S.P Isnijah; Blasius Hangkoso; Sri Sumartini (Research Center for Chemistry - LIPI, 1997)
The amine compounds are used excessively in chemical industry, mainly as a surfactant. Indonesia imports this compound in a large amount (14.000 tons). The secondary amine is an intermediate product of quartener amine which is known as a softener. This research is aimed to observe the chemical reaction of synthesizing secondary amine at laboratory scale.To achieve this goal, the synthesize was conducted by hydrogenating the nitrile compound in a reactor in which two levels of pressure were applied (11 and 35 bars). The reaction temperature as well as the length of reaction time were also varied i.e at 140°, 160° and 175° Cfor 3, 6 and 10 hours.The analytical results showed that at relatively low pressure (11 bars) and the reaction temperatures of 140°,160° and 175° C for 10 haurs gave products containing secondary amine as much as 48,90; 74,63 and 67,26%, respectively. The 6 hours processing time at 140°C did not produce any amine. However when temperature was increased to 160° and 175° C, the amounts of amine yielded are as follow: 46,40 and 73,33%. A higher result (85,80%) was obtained from a process conducted at reaction temperature 175° C for 3 hours.By increasing the pressure up to 35 bars and the reaction was maintained at 160°, 83,40% amine was produced in 1 hour only. This finding indicated that producing amine at lower pressure required longer processing time.